Strategi Pemasaran Dalam Meningkatkan Penjualan OMMA Swalayan Padang - Algusri, Jeki (LPPM Universitas Pelita Bangsa, 2025)
This research was conducted at Omma Swalayan Padang. The object of this research is the marketing strategy of Omma Swalayan. The purpose of this study is to identify the marketing strategies implemented by Omma Swalayan in selling its products and to explore the obstacles faced by Omma Swalayan Padang in the competitive market.This type of research is descriptive in nature. The data analysis method used is SWOT analysis. Based on the results of the research, the following conclusions were drawn:The strengths of Omma Swalayan Padang include its strategic business location.The weaknesses include the relatively new establishment of the business, the lack of promotional and advertising services, and limited business experience.The main opportunities for Omma Swalayan Padang include the opening of a new branch on Jl. Siteba Padang and the increasing needs of the local community.The major threats faced by Omma Swalayan Padang include the emergence of similar businesses and price competition in the same industry.In this context, Omma Swalayan Padang can apply a market penetration strategy. This strategy aims to increase the market share of a product or service through more intensive marketing efforts.